Development of Measuring System using CSI on ITIL V3 for Improvement at Oil Palm Plantation Company - Andry, Johanes; Wijaya, Careen Hany; Thomas, Kennedy (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
Many information technology services firms now offer services and consider software availability to be a critical component of achieving excellence and competing in the industry. The most crucial factor for customers is the quality of service, consumer needs, the state of the organization/company, and the present market should all be considered when improving their service. In this study, an ITSM analysis will be carried out at an oil palm plantation company based in West Kalimantan Province using ITIL framework V3 by focusing on continual service improvement, which largely relies on service measurement because a process must be measurable to be regulated and improved. To achieve continuous service improvement (CSI) throughout the service life cycle, we use the 7-step process to improve is used to establish and take care of the stages involved in identifying, defining, collecting, processing, analyzing, presenting, and implementing changes. The result of this analysis is CSF and KPI analysis that produce metrics, such as the average resolution time, the percentage of events allocated more than once, and the initial response time, then create a measurement system that is in accordance with the needs and can be used as a reference for the company's system assessment.